Стратегія адаптації до змін клімату як основа економічного розвитку агропідприємств та створення кліматично орієнтованої продовольчої системи - Карпенко, Андрій Володимирович; Левченко, Сергій Анатолійович; Karpenko, Andrii; Levchenko, Serhii (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті констатовано, що зміни клімату становлять серйозну загрозу для ля економічного розвитку агропідприємств та продовольчої системи. Проаналізовано сучасні наукові дослідження та практичні підходи з адаптації аграрного сектору до кліматичних змін. Обгрунтовано необхідність розробки Стратегії адаптації до змін клімату, яка б забезпечувала комплексний підхід до управління ризиками, ресурсами та виробничими процесами агропідприємств. Підкреслено, що її реалізація сприятиме формуванню кліматично орієнтованої та ресурсоефективної продовольчої системи. Наголошено, що фінансові стимули та розвиток інноваційних агротехнологій є ключовими чинниками успішної реалізації Стратегії з адаптації, а комплексне поєднання управлінських і адаптаційних заходів забезпечить впровадження інноваційних кліматично-орієнтованих бізнес-моделей та створення кліматично-орієнтованої продовольчої системи. /// EN: The article establishes that climate change poses a serious threat to the economic development of agricultural enterprises and the food system, particularly due to the increasing frequency of extreme weather events, droughts, and temperature fluctuations, which negatively affect crop yields and the efficiency of natural resource use. Contemporary scientific research and practical approaches to adapting the agricultural sector to climate change are analyzed. The necessity of developing a Climate Change Adaptation Strategy is substantiated, one that would ensure a comprehensive approach to managing risks, resources, and production processes of agricultural enterprises. It is determined that the Adaptation Strategy should integrate economic, technological, and environmental aspects; include the implementation of climate-smart practices; ensure precise management of water and land resources; promote the use of crop varieties resilient to climate risks; and incorporate agroforestry measures. It is emphasized that the implementation of the Adaptation Strategy should be accompanied by systematic monitoring of the effectiveness of measures, adjustment of priorities in accordance with changing natural and climatic conditions, and integration with national and international climate policy initiatives. The article highlights that the implementation of the Adaptation Strategy will increase agricultural productivity, optimize costs, and strengthen the financial resilience of agricultural enterprises under conditions of climate instability. It is underlined that its implementation will contribute to the formation of a climate-oriented and resource-efficient food system. It is stressed that state support, financial incentives, and the development of innovative agricultural technologies are key factors for the successful implementation of the Adaptation Strategy, while a comprehensive combination of managerial and adaptation measures will ensure the introduction of innovative climate-oriented business models and the establishment of a climate-oriented food system.
Climate change adaptation strategy as a foundation for the economic development of agricultural enterprises and the creation of a climate-oriented food system
Keywords: адаптація до змін клімату; кліматичні виклики; кліматичні зміни; адаптаційна стратегія; бізнес-моделі; кліматично орієнтована продовольча система; ресурсоефективна продовольча система; climate change adaptation; climate challenges; climate change; adaptation strategy; business models; climate-oriented food system; resource-efficient food system